The Implementation of Social and Religious Values in Learning at TK Kartini III Gilingan. - Muflikhah Siwi Arti; Puji Yanti Fauziah (UPI Kampus Cibiru, 2019)
Abstract:. This study aims to reveal implementation of social and religious values, at TK Kartini III Gilingan.This research is used qualitative approach. The data analysis used the descriptive analysis. The subject consists of the principal, teachers, and students of TK Kartini 03 Gilingan. The data collection is through interviews, observation, and documentation. The aspects of this research consist of learning materials, educators, methods, development of implementation, and the supporting and inhibiting factors in the implementation of social and religious values.The results show that, first the learning methods used for the implementation of social and religious values is storytelling, habituation, and singing, but the method actually applied in the implementation of social and religious values is only the habituation method. Second, learning materials used refers to Permendikbud 146 Year 2014. Of all the basic competencies written in Permendikbud 146 Year 2014, only few learning materials are developed. Third school environments are the most important factors, because the school is close to the localization area which has bad effects on children. Parents and educators expect cooperation programs from the local government and residents for a good management of the localization so as to provide the children a conducive environment.Keywords: religious and social values, learning activities